Paleomagnetic results from the Skaergaard intrusion, East Greenland (Dataset) ... - E.J. Schwarz; L.C. Coleman; H.M. Cattroll (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Paleomagnetic results from the Skaergaard intrusion, East Greenland ...